Long-term outcome predictors after functional remediation in patients with bipolar disorder. Issue 2 (16th January 2022) - Solé, B.; Bonnín, C. M.; Radua, J.; Montejo, L.; Hogg, B.; Jimenez, E.; Reinares, M.; Valls, E.; Varo, C.; Pacchiarotti, I.; Valentí, M.; Garriga, M.; et al.
Abstract: Background: Improving functioning in patients with bipolar disorder (BD) is one of the main objectives in clinical practice. Of the few psychosocial interventions that have been specifically developed to enhance the psychosocial outcome in BD, functional remediation (FR) is one which has demonstrated efficacy. The aim of this study was to examine which variables could predict improved functional outcome following the FR intervention in a sample of euthymic or subsyndromal patients with BD. Methods: A total of 92 euthymic outpatients were included in this longitudinal study, with 62 completers. Partial correlations controlling for the functional outcome at baseline were calculated between demographic, clinical and neurocognitive variables, and functional outcome at endpoint was assessed by means of the Functioning Assessment Short Test scale. Next, a multiple regression analysis was run in order to identify potential predictors of functional outcome at 2-year follow-up, using the variables found to be statistically significant in the correlation analysis and other variables related to functioning as identified in the previous scientific literature. Results: The regression model revealed that only two independent variables significantly contributed to the model ( F (6, 53) : 4.003; p = 0.002), namely verbal memory and inhibitory control. The model accounted for 31.2% of the variance. No other demographic or clinical variable contributed to the model. Conclusions: Results suggest that patients with better cognitive performance at baseline, especially in terms of verbal memory and executive functions, may present better functional outcomes at long term follow-up after receiving functional remediation.